Kepuasan Konsumen Terhadap Objek Wisata Tuur Ma’asering Di Kelurahan Kumelembuai Kecamatan Tomohon Timur Kota Tomohon - Rasuh, Aini Sisilia; Sendow, Martha Mareyke; Timban, Jean Fanny Junita (AGRI-SOSIOEKONOMI, 2023)
This study aims to find out how consumer satisfaction with tourist attractions Tuur Ma’asering. This research was conducted from October 2022 to January 2023. The data used are primary data and secondary data. Primary data is obtained from direct interviews with 30 respondents using a questionnaire, while secondary data is obtained from business owners, the internet and other sources that are relevant to this research. The results showed that customer satisfaction at Tuur Ma’asering tourism in Kumelembuai Village, Tomohon Timur District, Tomohon City through the variables of product, price, place, promotion and service quality, achieved a total score of 1,521 which indicates a consumer satisfaction index number of 84.5% and belong to the very satisfied category. The four variables that have the highest level of customer satisfaction are product, service, place/location, price, with the percentages (92.88%), (90.00%), (90.77%), (82.88%) belonging to very satisfied category. While the lowest variable is promotion with a percentage of 63.33% which belongs to the satisfied category. This shows that consumers are generally satisfied with all variables on the Tuur Ma’asering tour.